Brand Trust as Mediator for Interactivity, Informativeness, and Perceived Relevance in Purchase Decision - Faradhilla, Dien; Alimuddin, Arasy; Suyono, Joko; Widjanarko, Bambang (INNOVATION RESEARCH JOURNAL, 2024)
This study aims to analyze the influence of social media marketing features consisting of interactivity,informativeness, and perceived relevance on brand trust and purchasing decisions. The study alsoexamines the role of brand trust as a mediating variable. This study used a quantitative approach withstructural equation modeling analysis. Type of data used in this study is primary data using datasources in the form of questionnaires distributed to research samples. A q nged uestionnaire is a datacollection technique carried out by researchers through systematically arraquestions to be distributed torespondents who are the research sample. The number of samples was 187 respondents from afinancial company in East Java. There is significant influence social media marketing features consist ofinteractivity, informativeness, and perceived relevance on brand trust. There is significant influencesocial media marketing features consist of of interactivity, informativeness, and perceived relevance onpurchase decision. The interactivity, informativeness, and perceived relevance has a positive andsignificant effect on purchasing decisions through brand trust